Strontium isotope ratios of human hair from the United States: Patterns and aberrations. (15th February 2019) - Tipple, Brett J.; Valenzuela, Luciano O.; Chau, Thuan H.; Hu, Lihai; Bataille, Clement P.; Chesson, Lesley A.; Ehleringer, James R.
Abstract : Rationale: Strontium isotope ratios ( 87 Sr/ 86 Sr) of hair may be a valuable tool to estimate human provenance. However, the systematics and mechanisms controlling spatial variation in 87 Sr/ 86 Sr of modern human hair remain unclear. Here, we measure 87 Sr/ 86 Sr of hair specimens from across the USA to assess the presence of geospatial relationships. Methods: Ninety‐eight human hair specimens were collected from salon/barbershop floors in 48 municipalities throughout the conterminous USA. [Sr] and 87 Sr/ 86 Sr ratios were measured from hair using quadrupole and multi‐collector inductively coupled plasma mass spectrometers, respectively. The [Sr] and 87 Sr/ 86 Sr ratios of hair were compared with the measured [Sr] and 87 Sr/ 86 Sr ratios of tap waters from the collection locations. In addition, the 87 Sr/ 86 Sr ratio of hair was compared with the modeled ratios of bedrock and surface waters. Results: Hair color was independent of the 87 Sr/ 86 Sr ratio, but related to [Sr]. The 87 Sr/ 86 Sr ratios of hair and leachate were not statistically different and were positively correlated; however, in several hair‐leachate pairs, the ratios were conspicuously different. The 87 Sr/ 86 Sr ratios of both hair and leachate were linearly correlated with tap water. The 87 Sr/ 86 Sr ratio of hair was also significantly correlated with the modeled ratio of bedrock and surface waters, although the 87 Sr/ 86 Sr ratio of hair was most strongly correlated with the measured ratio of tap water. Conclusions: The 87 Sr/ 86 Sr ratio of hair is related to the ratio of tap water, which varied geographically. The ratio of hair provided geographic information about an individual's recent residence. Differences in the 87 Sr/ 86 Sr ratios of hair and hair leachate may be concomitant with travel and could potentially be used as a screening tool to identify recent movements.